Hydrophilicity Tunable Hyperbranched Polymers by Visible Light Induced Self‐Condensing Vinyl Polymerization - Bener, Semira; Aydogan, Cansu; Yagci, Yusuf (Wiley, 2019)
AbstractA facile and efficient route for synthesizing hydrophilicity tunable hyperbranched polymers is described. The method is based on the visible light induced self‐condensing vinyl copolymerization of tert‐butyl acrylate (tBA) and 2‐(2‐bromoisobutryloxy)ethyl methacrylate (BIBEM) as monomer and inimer, respectively, in the presence of dimanganese decacarbonyl (Mn2(CO)10). Subsequently, the hydrophlicity of the resulting hydrophobic hyperbranched polymers is tuned by hydrolysis of the tert‐butyl ester moieties of the copolymer. The effect of inimer concentration and irradiation time on the branching density and hydrophilicity is evaluated. The precursor and hydrolyzed hyperbranched polymers are characterized by 1H NMR, GPC, FT‐IR, and contact angle measurements.